KONTRADIKSI HUBUNGAN ANTARA TURNOVER INTENTION DENGAN TURNOVER: Kajian Penyebab Tingginya Turnover Intention dan Tidak Berpengaruhnya Turnover Intention terhadap Turnover - Affandi, Lutfy; Basukianto, Basukianto (Jurnal Ilmiah Telaah Manajemen, 2014)
Health workers in RSJD Dr. Amino Gondohutama Semarang has a highrate of turnover intention. This conditioncan negatively affect the development ofthe organization, even some of the figure sreveals that turnover intentionis amajor predictor of turnover. Interesting problem in RSJD Dr. Amino Gondohutama Semarang is the high turnover intention but not accompanied by decision turnover. The purposeof this researchis to analyzethe influence ofindividual characteristics, job stress and job satisfaction on turn overintention, and the relationship between turnover intention to decision turnover. Study sampleas many as166 people set health professionals working in RSJDDr. Amino Gondo hutama Semarang. The sampling technique used convenience sampling. Data obtained using a questionnaire, and then analyzed using multiple regression analysis and across tabanalysis. The results showed that the high turnover intention is caused by age, employment status, job stress, where as factors that decrease turnover intention is job satisfaction. Sex, education, marital status, and years of work no effect on turnover intention. Further more, turnover intention has no impact onturnover due to prestige as a major factor, future security, support colleagues, was unethical when out of work, good career opportunities, incentivesare worth, still under contract, it is difficult to find another job, and familial ties. Family bondis the weakestfactor. Keywords: individual characteristics, job stress, job satisfaction, decision turnover intention, turnover, health workers